Study of biochemical parameters in metabolic bone disease with chronic renal failure - Sathe, Chitra A.; Khamkar, Vinaya P. (International Journal of Research in Medical Sciences, 2016)
Background: Renal osteodystrophy and metabolic bone disease are terms that encompass a number of skeletal abnormalities, including osteomalasia, osteitis fibrosa cystica and impaired bone growth in children. The proposed work aimed to evaluate the status of bone health by estimating levels of elements like calcium, phosphorus, magnesium, alkaline phosphatase and alkaline phosphatase isoenzymes in serum of patients suffering from metabolic bone disease with chronic renal failure. Methods: The routine biochemical investigations were estimated by known standard methods and alkaline phosphatase isoenzymes were done by polyacrylamide slab gel electrophoresis. The assay values were statistically validated. Results: Serum calcium levels were significantly decreased (p<0.001) in chronic renal failure cases than control whereas, phosphorus and serum alkaline phosphatase levels were significantly increased. Electrophoresis on polyacrylamide gel separated the serum alkaline phosphatase isoenzymes. In control group, two bands of isoenzymes appeared. Whereas, in patients with metabolic bone disease with chronic renal failure, only one diffused band appeared. Conclusions: Decreased calcium levels and increased phosphorus levels in serum indicate metabolic bone disease with chronic renal failure. Elevation of serum alkaline phosphatase is a marker of sick bone. Increased levels of serum alkaline phosphatase are responsible for appearance of diffused band of isoenzyme which is marker for metabolic bone disease with chronic renal failure.